Heat transfer principles in thermal calculation of structures in fire - Zhang, Chao; Usmani, Asif (Fire safety journal, 2015)
Structural fire engineering (SFE) is a relatively new interdisciplinary subject, which requires a comprehensive knowledge of heat transfer, fire dynamics and structural analysis. It is predominantly the community of structural engineers who currently carry out most of the structural fire engineering research and design work. The structural engineering curriculum in universities and colleges do not usually include courses in heat transfer and fire dynamics. In some institutions of higher education, there are graduate courses for fire resistant design which focus on the design approaches in codes. As a result, structural engineers who are responsible for structural fire safety and are competent to do their jobs by following the rules specified in prescriptive codes may find it difficult to move toward performance-based fire safety design which requires a deep understanding of both fire and heat. Fire safety engineers, on the other hand, are usually focused on fire development and smoke control, and may not be familiar with the heat transfer principles used in structural fire analysis, or structural failure analysis. This paper discusses the fundamental heat transfer principles in thermal calculation of structures in fire, which might serve as an educational guide for students, engineers and researchers. Insights on problems which are commonly ignored in performance based fire safety design are also presented. •Applicability of lumped heat capacity method for insulated steel provided.•Member's location affects its temperature in a post-flashover fire compartment.•Heat sink effect of steel members in a fire compartment is considerable.•Theoretical model developed to calculate heat flux to horizontal members in large enclosure.•Theoretical model developed to calculate safe distance from a column to a localized fire.